2005
DOI: 10.1111/j.1398-9995.2005.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base equilibrium in exhaled breath condensate of allergic asthmatic children

Abstract: These data show that EBC pH values of stable asthmatic children are lower compared with those of healthy controls and positively correlated with ammonia concentrations, supporting the hypothesis that airway acidification may have a role in the pathobiology of allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 23 publications
8
56
0
1
Order By: Relevance
“…Normal values of gas-standardized ("CO 2 -free") EBC pH have been reported from multiple investigators and range between 7.5 and 8.1 (3,8,9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In our normative database from 404 subjects, the mean pH was 7.83, and the median pH was 8.0 (12).…”
Section: Normal Ebc Ph Valuesmentioning
confidence: 76%
“…Normal values of gas-standardized ("CO 2 -free") EBC pH have been reported from multiple investigators and range between 7.5 and 8.1 (3,8,9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In our normative database from 404 subjects, the mean pH was 7.83, and the median pH was 8.0 (12).…”
Section: Normal Ebc Ph Valuesmentioning
confidence: 76%
“…[7][8][9][10] As EBC deaeration itself is tedious, costly, and time-consuming, we chose not to deaerate samples prior to pH measurements in this study. The published literature was also divided in opinion regarding the necessity of this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…(i.e., acidic) in patients with asthma [7][8][9][10] and chronic cough. 11 However, only one of these studies looked into the relationship between asthma severity and EBC pH in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent data suggest a link between 8-isoprostane concentration in EBC and small airways inflammation [102]. Using different collection devices, several research groups found an average pH of 7.8 in the EBC of healthy subjects, whereas in asthma the average pH was found below 7.5 [103][104][105][106][107]. Asthma exacerbations have been shown to result in further decline of pH with reversal following corticosteroid treatment [107].…”
Section: Exhaled Breath Condensate (Ebc)mentioning
confidence: 99%